The Flash and Flesh of the Spirit. - Ames, Amelia (Liquid Blackness: Journal of Aesthetics & Black Studies, 2026)
This article analyzes Senga Nengudi's performance Masked Taping (ca. 1978/79). Adorning her body in pieces of white tape in a dark room, Nengudi moved rapidly before a camera to explore "elements of [her] African heritage of mask making." In so doing, white tape transformed her body into a literal flash of illumination for the camera, while simultaneously creating the visual effect of a spectral flash of a spirit. What, this article asks, is the relation between Nengudi's reclamation of such heritage and the camera? How did her use of technology transform how we understand a mask? To answer these questions, the article compares Robert Farris Thompson's notion of the "flash" in his 1983 classic Flash of the Spirit with Walter Benjamin's theorization of the resurgence of the mimetic faculty in the new visual technologies of modernity. Benjamin offers a way to rethink how mimesis — characteristic of the spirit world Nengudi aimed to "channel" in Masked Taping — returns not through an innate disposition of diasporic peoples but rather through Nengudi's critical use of mimetic technology. The radical legacy of Masked Taping, the article argues, lies in Nengudi's demonstration of how the ancestral arts are always already modern.